2015
DOI: 10.1016/j.jtcvs.2014.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose rosuvastatin ameliorates lung ischemia–reperfusion injury via upregulation of endothelial nitric oxide synthase and inhibition of macrophage infiltration in rats with pulmonary hypertension

Abstract: Single-dose rosuvastatin decreased IR injury in lungs affected by PH via 2 anti-inflammatory mechanisms: preserving eNOS function and inhibiting macrophage infiltration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…; Matsuo et al. ). As shown in Figure , the time‐dependent and similar increases in total and phosphorylated eNOS expressions suggest that most of the eNOS expression is in the active form in the established PAH.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…; Matsuo et al. ). As shown in Figure , the time‐dependent and similar increases in total and phosphorylated eNOS expressions suggest that most of the eNOS expression is in the active form in the established PAH.…”
Section: Discussionmentioning
confidence: 96%
“…3A). The levels of phosphorylated eNOS, a marker of increased eNOS activity (Matsuo et al 2015), were enhanced in the lungs at the 1-, 3-, 5-, and 8-week time points (Fig. 3B).…”
Section: Immunoblot Analysis Of Enos and Its Phosphorylation In Normamentioning
confidence: 93%
See 2 more Smart Citations
“…Macrophage infiltration into the wall of mesenteric resistance arteries is a common finding in DOCA-salt and ANG II-induced systemic hypertension (11,31,36). Macrophage infiltration into the wall of the pulmonary artery also occurs in animal models of pulmonary hypertension (45). Others (5,31,54) have found that macrophages infiltrate into the wall of the thoracic aorta in DOCA-salt, ANG II-infused, and stroke-prone spontaneously hypertensive rats, so the macrophage response may not be specific for MAs; however, macrophage infiltration into resistance arteries, other than MAs, has not been reported to our knowledge.…”
Section: Immune Activation In Hypertensionmentioning
confidence: 99%